Sinding-Larsen-Johansson disease. Clinical features, imaging findings, conservative treatments and research perspectives: a scoping review - Wilczyński,Bartosz; Taraszkiewicz,Marcin; de Tillier,Karol; Biały,Maciej; Zorena,Katarzyna (PeerJ, 2024)
Objective This review aims to consolidate existing research on the pathogenesis, clinical diagnosis, imaging outcomes, and conservative treatments of Sinding-Larsen-Johansson disease (SLJD), identifying literature gaps. Design Scoping Review. Methods A comprehensive literature search was conducted across databases including PubMed, Scopus, Medline OVID, Embase, Web of Science, and Grey literature following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) extension for scoping reviews. The quality of included studies was assessed using the Joanna Briggs Institute (JBI) checklist. Results The body of evidence on SLJD, primarily derived from case studies, reveals limited and often conflicting data. Key findings include: (1) SLJD commonly presents as localized knee pain in physically active adolescents, particularly males, (2) ultrasound and MRI are the most effective diagnostic tools, (3) conservative treatment, which mainly focuses on activity limitation, yields positive outcomes within two to eight months. Conclusions Our review shows that SLJD mainly affects physically active adolescents aged 9–17 years. The authors recommend conservative treatment, rest and/or cryotherapy, passive mobilization, muscle restraint, isometric exercise, and NSAIDs. Further cohort studies are necessary to refine the management and application of the SLJD treatment database.
Keywords: Osteochondrosis; Apophysis; Apophyseal injuries; Sinding-Larsen-Johansson disease; Youth atlhletes injury